2014
DOI: 10.1007/s00432-014-1627-1
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2: bane or blessing in cancer?

Abstract: This review aims to rationalize the existing functions of Nrf2 in chemoprevention and tumorigenesis, as well as the somatic mutations of Nrf2 and Keap1 in cancer and Nrf2 cross talk with miRNAs. This review also discusses the future challenges in Nrf2 research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 105 publications
0
40
0
1
Order By: Relevance
“…Despite intense scrutiny in cancer research studies, the precise mechanisms that control Nrf2 translocation remain poorly understood. 54 It is therefore difficult to propose a mechanism by which BDNF controls the Nrf2 pathway. Nevertheless, we have found that BDNF tonically induces Nrf2 translocation into the nucleus under basal conditions, thereby constantly activating antioxidant mechanisms.…”
Section: Upstream Regulation Of Nrf2mentioning
confidence: 99%
“…Despite intense scrutiny in cancer research studies, the precise mechanisms that control Nrf2 translocation remain poorly understood. 54 It is therefore difficult to propose a mechanism by which BDNF controls the Nrf2 pathway. Nevertheless, we have found that BDNF tonically induces Nrf2 translocation into the nucleus under basal conditions, thereby constantly activating antioxidant mechanisms.…”
Section: Upstream Regulation Of Nrf2mentioning
confidence: 99%
“…This is based on the dissociation of NRF2 from KEAP1 in the cytoplasm leading to the translocation of NRF2 into the nucleus where it dimerizes with sMAF proteins, and then binds to ARE-carrying promoters to subsequently initiate the gene expression of cytoprotective and detoxifying enzymes [60,66] . The activation of the phosphoinositide 3-kinases (PI3K)/Akt signalling pathway and stresses on the endoplasmic reticulum are some of the mechanisms that can lead to nuclear accumulation of NRF2 and increased ARE-driven gene expression [60,67,68] . The non-canonical interacts with NRF2 in the cytosol, promoting its polyubiquitylation and subsequent proteasomal degradation by the substrate adaptor for cullinbased E3 ubiquitin ligase complex, resulting in little NRF2 that is sufficient for the maintenance of cellular homeostasis or absence of NRF2 transactivation; B: In contrast, under oxidative stress conditions, the binding of KEAP1 to NRF2 is greatly impaired to compromise the likelihood of NRF2 ubiquitylation.…”
Section: Nrf2 Signalling Pathway and Regulationmentioning
confidence: 99%
“…Persistent, excess Nrf2 activation, such as by Keap1 knockout, has been associated in laboratory studies with (11,46,109) Cancer (63, 67, 109) Heart disease (48,72) Heart disease (70) Liver disease (56,57) Liver disease (110,111) Viruses (59,112,113) Viruses (58) Lung disorders (36,(51)(52)(53)(54)(55) Atherosclerosis (114) Parkinson's disease (38)(39)(40) Huntington's disease (41,42) Amyotrophic lateral sclerosis (43) Multiple sclerosis (44,45) Diabetes (47) Kidney diseases (49,50) Nrf2, nuclear factor erythroid 2-related factor 2.…”
Section: Nrf2 and Reductive Stressmentioning
confidence: 99%